Agronomic performance and silage quality traits of forage sorghum hybrids in 1992 - Sonon, R.N.; Dalke, B.S.; Holthaus, D.L.; Bonilla, D.R.; Pfaff, L.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rainfall was much above and temperature much below normal during the 1992 growing season. Both whole-plant dry matter (DM) and grain yields were excellent for all 11 hybrids. The two short, mid-maturing, forage sorghums (Northrup King 300 and Golden Harvest H-45) had the highest silage and grain yields; the early-maturing (Cargill 200F) and male sterile (Golden Harvest H-1) forage sorghums and the grain sorghum (DeKalb DK 42Y) the lowest silage yields. A storm with high winds on October 7 and 8 caused severe lodging in all six mid- and late-maturing hybrids (earlier-maturing hybrids had already been harvested). The 10 forage sorghum hybrids differed significantly in three important silage quality traits—whole-plant DM, crude protein, and acid detergent fiber. Silage agronomic performance for four of the forage sorghums over 6 of the past 7 years is presented.
Keywords: Beef; Forage sorghum; Hybrid; Silage; Yield